Jasmonic acid negatively regulates branch growth in pear - Cheng, Yuanyuan; Liang, Chenglin; Qiu, Zhiyun; Zhou, Siqi; Liu, Jianlong; Yang, Yingjie; Wang, Ran; Yin, Jie; Ma, Chunhui; Cui, Zhenhua; Song, Jiankun; Li, Dingli (Frontiers in Plant Science, 2023)
The quality of seedlings is an important factor for development of the pear industry. A strong seedling with few branches and suitable internodes is ideal material as a rootstock for grafting and breeding. Several branching mutants of pear rootstocks were identified previously. In the present study, ‘QAU-D03’ (Pyrus communis L.) and it’s mutants were used to explore the mechanism that affects branch formation by conducting phenotypic trait assessment, hormone content analysis, and transcriptome analysis. The mutant plant (MP) showed fewer branches, shorter 1-year-old shoots, and longer petiole length, compared to original plants (OP), i.e., wild type. Endogenous hormone analysis revealed that auxin, cytokinin, and jasmonic acid contents in the stem tips of MP were significantly higher than those of the original plants. In particular, the jasmonic acid content of the MP was 1.8 times higher than that of the original plants. Transcriptome analysis revealed that PcCOI1, which is a transcriptional regulatory gene downstream of the jasmonic acid signaling pathway, was expressed more highly in the MP than in the original plants, whereas the expression levels of PcJAZ and PcMYC were reduced in the MP compared with that of the original plants. In response to treatment with exogenous methyl jasmonate, the original plants phenotype was consistent with that of the MP in developing less branches. These results indicate that jasmonic acid negatively regulates branch growth of pear trees and that jasmonic acid downstream regulatory genes play a crucial role in regulating branching.